IgG subclass deficiency in asthma. Issue 12 (December 1988) - Loftus, B G; Price, J F; Lobo-Yeo, A; Vergani, D
Abstract : Total immunoglobulin G (IgG) and subclasses were measured in serum samples from 82 children with chronic asthma, aged 1.5 to 6.3 years, and 76 controls. Concentrations of IgG1, IgG2, IgG3, and total IgG were significantly lower in asthmatic children aged 1 to 5, and IgG2 concentrations were also significantly lower in asthmatic children over 5 years of age. Twenty eight asthmatic children had at least one value in the deficient range, and 26 had IgG2 deficiency alone or in combination. Five children had IgG2 and IgA deficiency. These 28 children were significantly younger and fewer had raised IgE concentrations than the remainder. IgG subclass deficiency, which may reflect delayed maturation of the immune system, is common in young asthmatic children, and may have a role in the pathogenesis of the disease.